Peningkatan Arus Kas berdampak terhadap Tingkat Likuiditas Perusahaan pada PT Indofood CBP Sukses Makmur Tbk Periode 2008-2017 - Mochamad Syaiful Ramadan; Titim Cahyani (LPPM POLITEKNIK LP3I BANDUNG, 2019)
Based on the results of statistical analysis it is known that the level of liquidity of the company during the period 2008 to 2017 has increased and decreased from year to year. The average increase and decrease in the level of company liquidity occurs once a year. But there is also a decrease that occurred 2 years in a row namely in 2016 amounted to 150,813% and in 2017 amounted to 150,272% which initially in 2015 the company's liquidity level was 170,533%. So there is a significant decrease from that year. Then the company's cash flow from 2008 to 2014 has increased, which is also accompanied by ups and downs of the company's current debt. Whereas from 2014 to 2015, the company's cash flow decreased initially from Rp14,157,805 to Rp12,962,041. However, in the following years, cash flow increased again, in 2016 the company's net cash flow was Rp. 13,362,236, and in 2017 the company's net cash flow was Rp. 13,689,998. And Cash Flow (X) of PT. Indofood CBP Sukses Makmur Tbk. significant effect on the Liquidity Level (Y) of the company from 2008 to 2017, with a significance level of 0.014.